An Emergency Powered Air-Purifying Respirator From Local Materials and its Efficacy Against Aerosolized Nanoparticles - Jeff Kessel MD; Christopher S. Saevig; W. Cary Hill PhD; Benjamin Kessel; Matthew S. Hull PhD (SAGE Publishing, 2022)
We describe an approach used by a rural healthcare provider to convert surgical helmets into emergency powered air-purifying respirators (PAPRs) at the onset of the COVID-19 pandemic. The approach uses common materials and efficacy was demonstrated against aerosols measuring 7 nm to 25 μm in diameter.